Human gamma interferon and tumor necrosis factor exert a synergistic blockade on the replication of herpes simplex virus. - Feduchi, E (1989)
The replication of herpes simplex virus type 1 (HSV-1) is not inhibited in either HeLa or HEp-2 cells treated with human alpha interferon (HuIFN-alpha), particularly when high multiplicities of infection are used. However, HuIFN-gamma partially inhibits HSV-1 translation in HEp-2 cells infected at low multiplicities. Under these conditions, the transcription of genes alpha 22, TK, and gamma 0 is greatly diminished. The combined addition of human tumor necrosis factor (TNF) and HuIFN-gamma to HEp-2 cells exerts a synergistic inhibition of HSV-1 translation. Cells treated with both cytokines continue synthesizing cellular proteins, even 20 h after HSV-1 infection. As little as 10 U of IFN-gamma per ml blocked HSV-1 DNA replication, provided that TNF was also present in the medium. Analyses of HSV-1 gene transcription suggest that the action of both TNF and IFN-gamma blocked a step that comes at or prior to early HSV-1 gene expression. This early step in HSV-1 replication inhibited by TNF and IFN-gamma occurs after virus attachment and entry into cells, since the internalization of radioactive HSV-1 virion particles was not blocked by the presence of the two cytokines. Therefore, we conclude that the synergistic action of TNF plus IFN-gamma affects a step in HSV-1 replication that comes after virus entry but before or at the transcription of immediate-early genes.